Upzoning and value capture: How U.S. local governments use land use regulation power to create and capture value from real estate developments. (June 2020) - Kim, Minjee
Highlights: Major U.S. cities are securing public benefits from real estate developments through a variety of zoning techniques. There were two distinct components underlying the zoning techniques used for value capture: value addition and value capture. Some cities relied heavily on project-by-project negotiations for value creation and capture. Value capture strategies can be customized to adapt to unique local contexts. U.S. cities lack standards or evaluation framework for determining how much value is being created and what can be asked for in return. Abstract: The public sector can harness its authority to control land uses to secure valuable public benefits from real estate developments. This paper investigates how five major U.S. cities—Boston, Chicago, New York, San Francisco, and Seattle—are using their land use regulation powers to create and capture value for the public benefit. An analysis of the zoning and entitlement processes of the 20 largest real estate development projects in each city reveals that value has been captured from all 100 projects. Furthermore, these cities implicitly differentiated value capture into two distinct components: value creation and value capture. Among the 100 projects, cities created value for 90 projects by allowing greater density and height—a practice often referred to as "upzoning." Distinguishing such upzoning incidences from traditional land use exaction tools is important because the added value gives local governments greater legitimacy in asking for public benefits. The experience of the five cities further revealed that value capture strategies can be customized to adapt to unique regulatory, political, and cultural contexts. Lastly, despite the fact that the majority of the upzoned projects increased density and height through project-specific negotiations, none of the cities had clear standards or evaluation frameworks for determining: how much value was created, what can be asked for in return, and who should benefit from the value captured. Cross-national scholarship on value capture can be leveraged to address these important questions.